Pemodelan Deterministik Streeter-Phelps Untuk Evaluasi Kapasitas Self-Purification Dan Dinamika Oksigen Terlarut Pada Sungai Jagir Kota Surabaya - Ariesta Sulistyo Asih; Hikmal Akbar Habibie (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The Jagir River in Surabaya City faces critical ecological pressure due to the accumulation of urban wastewater along a 10 km segment from Wonokromo to Wonorejo. This study evaluated the River Water Pollution Load Capacity (RWPLC) and its natural self-purification capacity using the static mass balance method and Streeter-Phelps deterministic modeling. The baseline analysis revealed a total capacity deficit for Total Phosphorus (peaking at -628.99 kg/day in the middle segment) and a COD deficit of -4,354.56 kg/day in the downstream. Conversely, BOD, TSS, and the DO Sag Curve profile remained safe, with a minimum critical Dissolved Oxygen (DO) of 5.557 mg/L downstream (Mangrove Area) driven by high natural reaeration and rapid stream velocity (u = 4.51 m/s). Simulations proved that the 50% BOD Load Reduction Scenario is the most effective intervention to permanently eliminate oxygen deficits. Governance policies are recommended to focus on preventive strategies through strict industrial effluent regulation.